Movement errors during skilled motor performance engage distinct prediction error mechanisms - Ella Gabitov (Communications Biology, 2020)
Ella Gabitov et al. use functional magnetic resonance imaging to identify changes in neural activity when participants commit an error in a motor sequence task. Their results suggest that two distinct neural circuits are involved in the processing of action errors: (1) the salience network that signals surprise and novelty, and (2) the reward pathway that plays a central role in motivation and incentive drive.